Job generation and regional industrial policy in Ireland - Meyler, Aidan; Strobl, Eric (Economic & Social Studies, 2000)
Irish industrial policy explicitly encouraged job generation in certain ?designated? areas via, amongst other things, preferential grant treatment, job targets and the building of advance factories in the IDA?s (Industrial Development Authority) regional industrial plans of 1973-1977 and 1978-1982. To assess the impact of these regional plans, this paper compares the employment performance of the designated and the non-designated areas in Ireland since 1972 by employing the job flow methodology pioneered by Davis and Haltiwanger (1992). We find that the convergence in aggregate industrial employment levels between designated and non-designated areas observed since 1972 has been largely driven by a higher rate of job creation without an accompanying higher rate of job destruction in the designated areas. Our econometric study attributes an annual 27 per cent of the job generation in the designated areas during the relevant period to the explicit regional industrial policy.
Keywords: Industrial policy; Regional policy; Ireland; Job creation; Employment